The Effect of Applying the Role Playing Learning Model to Improve Students' Cognitive on Civics Material in Class VIII MTsN 02 Muara Bungo in 2021-2022 - Rapida (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2023)
The application of the Role Playing learning model to improve students' cognitive, in the material on the Principles of Unity in Diversity, aims to improve students' cognitive. Researchers use Student Discovery Sheets to direct learning activities according to the steps of the Role Playing model. This research activity was carried out at MTsN 02 Bungo, in the 2021-2022 academic year. Role Playing learning process can improve students' cognitive, fun and right on target. This study intends to determine the effect of applying the Role Playing model. The results are very significant affect the cognitive level of students. This Classroom Action Research (CAR) uses the Role Playing learning model in class which is carried out in the stages of planning, implementing, and observing, then reflecting for two cycles. Each cycle consists of three meetings. The research subjects in this PTK were 31 students in class 9C. The results of the research can be described that the Role Playing model and its application through Student Guide Sheets can be useful in directing students in learning activities that can improve their cognitive. The usefulness of this model is known from learning evaluation and increasing cognitive learning outcomes. Judging from the results of UH 1, 2, and 3, each cycle of students. The results of the first cycle test showed that only 19 out of 32 students achieved a score of ≥ 65 or 61.67% of students achieved the KKM. The results of the second cycle test showed that there were 28 out of 32 students who scored ≥65 or 82.35% of students achieved the KKM. The description of the achievement of students' cognitive improvement in cycle 1 can be explained by very good categories of 14.7% and good 41.17% while 2.94% and less 41.17%. The description of the achievement of students' cognitive improvement in cycle 2 can be explained by very good categories of 50%, good 29.41%, quite good 0%, and not good 20.58%.